PENGEMBANGAN MEDIA AUDIO VISUAL MELALUI PEMBELAJARAN BAHASA INDONESIA DI SDI KOAWENA - Yuinta Aurelia Nggua; Theresia Jelita Daghe; Maria Rosalina Meo; Maria Margareta Aadelia Uran; Yohanes Pedrico Seu sega; Bernadus Bolet (JURNAL PENGABDIAN MANDIRI, 2024)
This simulation is motivated by the world of education now continuing to keep up with the times to attend various education in the learning process. One of them is by using audio-visual media as learning media. This simulation aims to describe the use of audio-visual media in Indonesian language learning in class IV SDI Koawena, and the supporting and inhibiting factors in the use of audio-visual media in learning. This simulation uses a qualitative approach. The subjects of this simulation are class IV students at SDI Koawena. The simulation results show that the implementation of Indonesian language learning using audio-visual media is running in accordance with the teaching module that we created, the learning components have also been fulfilled to the maximum. There are still a few obstacles, such as not having an LCD, which makes the learning process unpleasant due to the limited tools used